ANALISIS PERBEDAAN PRODUKTIVITAS KERJA KARYAWAN TETAP, KONTRAK DAN PEKERJA HARIAN LEPAS (PHL) DI PDAM KOTA BENGKULU - Ida Anggriani; Aan Ramadhan Saputra (UNIVED Press, 2019)
The purpose of this study was to analyze and determine the differences in work productivity between employees, contracts and freelancers at PDAM of Bengkulu City.The research method used in this research is descriptive and comparative method. Respondents were 148 employees of PDAM Bengkulu city, consisting of 68 employees, 65 contract workers and 15 freelance workers. Data were collected by distributing questionnaires to respondents, data analysis was done using one-way anova (one-way anova) test, which was used to test the average comparison between several groups of data. The results showed that there were significant differences in work productivity between permanent employees, contract workers and freelancers at PDAM Bengkulu city (sig 0.002> 0.05). Descriptive statistics show that the average work productivity score of permanent employees is 91.75, the average work productivity of contract workers is 98.14 and the average work productivity of freelance workers is 95.14. These results indicate that contract workers’ productivity is more dominant than the other two groups of employees. Furthermore, freelance workers have the second highest average work productivity, while permanent employees have work productivity with the lowest average value compared to the other two groups.